Eksplorasi Faktor-Faktor Kepuasan Pengguna Asuransi Mandiri InHealth: Perspektif Internal Pengelola Program - Ida Ayu Nuh Kartini; Mariana Peka Powo; Nico Api Sunda; Debora Kristian (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the factors that influence the satisfaction of Mandiri InHealth Insurance users among holders of Mandiri InHealth life and health insurance cards. User satisfaction is a crucial indicator in evaluating the success of health insurance services, particularly in the context of corporate partnerships. This study employs a quantitative approach, utilizing a survey method directed at Mandiri InHealth employees and staff, who are both users of Mandiri InHealth Insurance and the personnel responsible for providing life and health insurance services to corporations that utilize InHealth Insurance.The factors analyzed included the quality of service, ease of claims, speed of service, insurance benefits, and reliability of information. The results of the study indicate that all independent variables have a significant impact on user satisfaction. These findings are expected to serve as a basis for evaluation for insurance providers in enhancing service quality.